2021
DOI: 10.3390/ijms222312797
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism-Associated Dyslipidemia: Potential Molecular Mechanisms Leading to NAFLD

Abstract: Thyroid hormones control lipid metabolism by exhibiting specific effects on the liver and adipose tissue in a coordinated manner. Different diseases of the thyroid gland can result in hypothyroidism. Hypothyroidism is frequently associated with dyslipidemia. Hypothyroidism-associated dyslipidemia subsequently results in intrahepatic accumulation of fat, leading to nonalcoholic fatty liver disease (NAFLD), which leads to the development of hepatic insulin resistance. The prevalence of NAFLD in the western world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 90 publications
1
37
0
5
Order By: Relevance
“…A recent study demonstrated that positive association between the urine levels of phthalate metabolites and NAFLD was observed in adults with subclinical hypothyroidism, but not in those with euthyroidism ( 30 ). In fact, evidence of a higher prevalence of NAFLD in patients with hypothyroidism has been detailed recorded in previous literature ( 23 , 31 ). Thyroid hormones mainly activate TH-Receptor β, a potential target in NAFLD therapy, and thus may improve liver steatosis ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 73%
“…A recent study demonstrated that positive association between the urine levels of phthalate metabolites and NAFLD was observed in adults with subclinical hypothyroidism, but not in those with euthyroidism ( 30 ). In fact, evidence of a higher prevalence of NAFLD in patients with hypothyroidism has been detailed recorded in previous literature ( 23 , 31 ). Thyroid hormones mainly activate TH-Receptor β, a potential target in NAFLD therapy, and thus may improve liver steatosis ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 73%
“…Трийодтиронін зумовлює посилення регуляції рецепторів ЛПНЩ, контролює стерол-регуляторний білокзв'язуючий елемент-2 (SREBP-2), який, у свою чергу, модулює експресію гена рецептора ЛПНЩ і захищає ЛПНЩ від окиснення. Гормони щитоподібної залози впливають на метаболізм ЛПВЩ, підвищуючи активність білка, що переносить складні ефіри холестерину (cholesterol ester transfer protein, СЕТР) та стимулює ліпопротеїнліпазу, яка катаболізує ліпопротеїни, багаті на ТГ, печінкову ліпазу і сприяє перетворенню ліпопротеїнів проміжної щільності в ХС ЛПНЩ [11].…”
Section: таблиця 5 виявлення атеросклеротичного ураження в групах поп...unclassified
“…Researchers also found that higher serum TSH and lower FT4 concentrations were significantly associated with steatosis and fibrosis in NAFLD [11 , 12] . Hypothyroidism-induced NAFLD has been attributed to decreased lipid utilization, including reduced β-oxidation of free fatty acids (FFAs) and the clearance of TGs, with a consequent increase in the accumulation of TGs and low-density lipoprotein within hepatocytes [13] . Moreover, hypothyroidism is correlated with hepatic insulin resistance, which fails to suppress the production of endogenous glucose and stimulates DNL [14] .…”
Section: Introductionmentioning
confidence: 99%